Analysis of Factors Influencing the Number of Poor People on the Island of Sumatra - Sukma Wardani; Eka Dewi Anggraini (Fakultas Ekonomi Dan Bisnis, Universitas Bengkulu, 2023)
This research aims to analyze the factors that influence the number of poor people in the Sumatra region. The data used is secondary data from the Central Statistics Agency in the 2013-2023 period. The dependent variable is the number of poor people in the current year, the independent variables are the previous year's Gross Regional Domestic Product, the previous year's economic growth, the previous year's poverty trap, and the previous year's capital expenditure. The data analysis method applied is panel data regression analysis with a fixed effect model. The research results show that Gross Regional Domestic Product and economic growth have a negative and significant effect, while the poverty trap and capital expenditure have a positive and significant effect on the number of poor people on the island of Sumatra.